Experience Trumps Stress in Shaping Audit Judgment Dynamics: Pengalaman Menghadapi Tekanan dalam Membentuk Dinamika Audit Judgment - Herawati, Nindy Maylinda; Biduri, Sarwendah (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract—Auditors play a critical role in ensuring the integrity of financial reporting, yet their performance is often influenced by various psychological and situational factors. While existing literature has explored the effects of work stress and self-efficacy on professional judgment, a gap remains in understanding the nuanced relationships between these variables in the context of audit judgment. This study aims to determine the effects of work stress, audit experience, and self-efficacy on audit judgment among active auditors in Surabaya's public accounting offices. Using a quantitative survey approach, data were collected from 40 auditors across eight public accounting firms, analyzed through multiple linear regression with SPSS. Results indicated that work stress does not significantly affect audit judgment, while audit experience positively influences it. Conversely, self-efficacy was found to have no significant impact on audit judgment. The novelty of this research lies in its focused examination of the interplay between these factors within the auditing profession, contributing to a better understanding of the conditions that affect auditors' decision-making. Implications the study suggests that improving auditors' experiences and addressing work stress and self-efficacy can enhance their judgment capabilities, thus improving audit quality. Further research is needed to explore additional variables. Highlights: Experience enhances audit judgment quality among auditors. Work stress does not significantly impact judgment quality. Self-efficacy has minimal influence on audit judgment outcomes. Keywords: Audit Judgment, Work Stress, Audit Experience, Self-Efficacy, Public Accounting